Broadening horizons: microbiota as a novel biomarker and potential treatment for endometriosis - Wang, Min; Liu, Wei; Zheng, Lianwen; Ma, Shuai; Jin, Lianhai; Zhao, Donghai; Li, Dandan (Frontiers in Microbiology, 2025)
As a heterogeneous disease, endometriosis is associated with diagnostic delay. Delayed diagnosis, physical discomfort, hormone therapy, and inconvenience in daily life and work all contribute to a decreased quality of life for endometriosis patients. Early clinical diagnosis is highly important for the intervention and treatment of endometriosis. Currently, reliable non-invasive diagnostic methods are lacking, and laparoscopic examination combined with pathological diagnosis is considered the “gold standard” for definitively diagnosing endometriosis. An increasing number of studies have confirmed the correlation between endometriosis and microbial ecological changes. Microbial dysbiosis is an important factor in the development and progression of endometriosis. Certain key microbial species and their metabolites can induce functional alterations in endometrial cells through various mechanisms, often preceding the emergence of clinical symptoms. Endometriosis are chronic inflammatory diseases, with an immunoinflammatory response as the pathological foundation. The microbiome may participate in the pathological mechanisms of endometriosis through multiple pathways, including mediating inflammatory responses, regulating immune responses, participating in estrogen regulation, interfering with metabolic activities, and modulating the gut–brain axis. Therefore, the microbiome holds potential as an early non-invasive diagnostic and therapeutic target for endometriosis patients. This study summarizes and analyses the correlations between microorganisms and their metabolites and the onset of endometriosis, aiming to provide novel insights into the etiology, diagnosis, and treatment of endometriosis.